Tracking evolving views of the 2024 Atlantic hurricane season with an expert prediction market - Roulston,M; Kaivanto,K; Toumi,R (Weather, 2025)
Before the 2024 Atlantic hurricane season began, the consensus was that it would be one of the most active seasons in history. However, a prolonged quiet period during late August and early September possibly led forecasters to question these predictions, before later activity fulfilled the season’s high expectations. The CRUCIAL initiative ran a ‘prediction market’ during 2024 which allowed experts to bet on the number of hurricanes. Prices in this market provide an insight into how views changed during the season. Prediction markets can efficiently aggregate the judgements of multiple experts and provide more up-to-date information than periodically issued forecasts.